Lecturers and Students Perception of Using a Study Guide - Ahmad Jafari; Mandana Shirazi; Hajar Ahmadi; Maryam Safarnavadeh; Mahdi Soroush (Kerman University of Medical Sciences, 2014)
Background & Objective: Today using new educational strategies and methods is of great importance Using a study guide is one of these new methods of teaching and learning The aim of the present study was to evaluate the perception of lecturers and students of the School of Dentistry Tehran University of Medical Sciences Iran toward the use of a study guide   Methods: In this quasiexperimental study 25 students of the School of Dentistry of Tehran University of Medical Sciences who had chosen the community dentistry course were randomly selected A study guide was given to students before their briefing session and 2 sessions in the school A questionnaire was designed in order to collect data on the perception of students toward the study guide and was used after the completion of the course The validity and reliability of the questionnaire were verified The questionnaire was also filled out by a professor of the Department of Oral Health Data was analyzed by SPSS software   Results: The survey of the students and lecturers perception of the study guide showed that 765% and 86% respectively chose agree and completely agree with the use of the study guide options   Conclusion: Using the study guide was rated as a suitable method thus it can be used to help students in the efficient use of training time